CulturePad: Linking indigenous communities to schools and education through the use of mobile technologies - Campbell, A.; Pagram, J.; Cooper, Martin (2016)
Information and communications technologies (ICT) are seen as crucial in improving educational opportunities and outcomes for children in remote communities. Yet these technologies are often viewed with suspicion by Indigenous communities in allowing access to material seen as potentially damaging to local culture such as gambling and pornography. This paper will discuss a project that attempted to forge strong links between community and school by engaging Indigenous children in literacy learning activities aimed at preserving local Indigenous culture through the use of mobile technologies. The results indicated that to achieve these aims the key school personnel were the Aboriginal Education Workers as they form the link between the school and the local community.